2022
DOI: 10.1142/s0219455423500438
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Damage Identification Based on Tuning-Free Strategy and Simple Population Metropolis–Hastings Algorithm

Abstract: The most commonly used method for sampling damage parameters from the posterior distribution is the Markov chain Monte Carlo (MCMC) method. The population MCMC method as one of the MCMC methods has been utilized for damage identification by some researchers recently. Nevertheless, for the conventional population MCMC methods, these sampling methods often require significant computational resources and tuning of a large number of algorithm parameters. Aiming at the problem of difficulty in selecting the proposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The finite element analysis results showed that this method provided a reliable tool for damage diagnosis under the premise of considering the uncertainty in the monitoring process. Luo et al [185] proposed an improved method for the MH algorithm to facilitate the rapid selection of proposal distribution in MCMC methods and to enhance computational efficiency. The proposed method employs an interchain communication mechanism among the simple population and utilizes a tuning-free strategy to simplify the algorithm.…”
Section: Bayesian Methodsmentioning
confidence: 99%
“…The finite element analysis results showed that this method provided a reliable tool for damage diagnosis under the premise of considering the uncertainty in the monitoring process. Luo et al [185] proposed an improved method for the MH algorithm to facilitate the rapid selection of proposal distribution in MCMC methods and to enhance computational efficiency. The proposed method employs an interchain communication mechanism among the simple population and utilizes a tuning-free strategy to simplify the algorithm.…”
Section: Bayesian Methodsmentioning
confidence: 99%
“…In an effort to enhance the safety and reliability of bridges and minimize the incidence of bridge collapse accidents, numerous scholars and experts have conducted comprehensive statistical investigations into the causes of bridge collapses [13][14][15]. The study of bridge collapse encompasses several disciplines, such as structural engineering, monitoring technology [16,17], transportation, and earthquake engineering, among others, and research methods employed in this area include theoretical analysis, experimental testing, numerical simulation, and case studies. The New York State Department of Transportation has established a comprehensive database comprising more than 428 collapsed bridges in the United States from 1992 to 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in Section 5, several conclusions and outlooks have been put forward. According to the dynamic theory, the free vibration equation of a civil engineering structure can be mathematized as follows [31]:…”
Section: Introductionmentioning
confidence: 99%